(The complaint in the poetry of Abu Ishaq al-Ghazi (441 e-524 (ALUSTATH JOURNAL FOR HUMAN AND SOCIAL SCIENCES, 2019)
The topic of the present research focuses on a critical issue that analyzes the content of (the complaint in the poetry of Abu Ishaq Al-Ghazi: an artistic-subjective study). Where he was able to be stronger to that load. Yes! There was complaint to difficulty of life, and his ignorance with human values to find out that time is the best advisor for him. He also complained about alienation, meanness, and poverty which were forced on him by life circumstances of that time. This research also addresses other complaints connected with social characteristics that featured the life of his time. Therefore, he complained about people estrangement, their harshness and their severe hypocrisy. Additionally, he complained the recession of poetry during that age, and being underestimated by his audience including: the kings, ministers and rulers. As a result of that, he wasn’t given the place he really deserved in their literary gatherings, and he was neither allowed to be close to them nor be given their gifts.The research also records the most remarkable artistic features of Al-Ghazi's poetry. It has been noted that he was just as competent as ..... His language was eloquent regarding both the words and the meanings, and he drew his poetic metaphors and images creatively. Also he used religious intertextuality as he cited many times from the Holy Quran. Besides that, he was inspired by the literary inheritance of the formers' poetry which was significantly noticed in his poems. He also employed traditional proverbs with its connotations and structure. In fact, one thing that distinguishes his works is the overuse of his poetic descriptions and his complex artistic similes.